Cycling the hot CNO: a teaching methodology. (22nd December 2017) - Frost-Schenk, J W; Diget, C Aa; Bentley, M A; Tuff, A
Abstract: An interactive activity to teach the hot Carbon, Nitrogen and Oxygen (HCNO) cycle is proposed. Justification for why the HCNO cycle is important is included via an example of x-ray bursts. The activity allows teaching and demonstration of half-life, nuclear isotopes, nuclear reactions, protons and α -particles, and catalytic processes. Whilst the process example is specific to astrophysics it may be used to teach more broadly about catalytic processes. This practical is designed for use with 10–20 participants, with the intention that the exercise will convey nuclear physics principles in a fun and interactive manner.